2011
DOI: 10.4007/annals.2011.173.3.7
|View full text |Cite
|
Sign up to set email alerts
|

The conjugacy problem in ergodic theory

Abstract: All common probability preserving transformations can be represented as elements of MPT, the group of measure preserving transformations of the unit interval with Lebesgue measure. This group has a natural Polish topology and the induced topology on the set of ergodic transformations is also Polish. Our main result is that the set of ergodic elements T in MPT that are isomorphic to their inverse is a complete analytic set. This has as a consequence the fact that the isomorphism relation is also a complete anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
159
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(162 citation statements)
references
References 16 publications
(15 reference statements)
1
159
2
Order By: Relevance
“…The purpose of this paper is to prove that this is indeed the case: This also answers a question raised by Kechris in [9, p. 123, (IIIb) and (IVb)], who asked if unitary equivalence of probability measure preserving actions of Γ is Borel. We note that Theorem 1.1 stands in contrast to the recent result of Foreman et al [4], who have shown that the conjugacy relation on ergodic transformations in the group of measure preserving transformations Aut(X, μ) is complete analytic, and so cannot be Borel, when (X, μ) is a standard non-atomic probability space. The paper is organized as follows: First, in Section 2, we will recall various basic notions from the theory of von Neumann algebras and the direct integral theory of unitary representations, and establish a simple lemma that will facilitate hierarchy complexity calculations later.…”
Section: Introductioncontrasting
confidence: 63%
“…The purpose of this paper is to prove that this is indeed the case: This also answers a question raised by Kechris in [9, p. 123, (IIIb) and (IVb)], who asked if unitary equivalence of probability measure preserving actions of Γ is Borel. We note that Theorem 1.1 stands in contrast to the recent result of Foreman et al [4], who have shown that the conjugacy relation on ergodic transformations in the group of measure preserving transformations Aut(X, μ) is complete analytic, and so cannot be Borel, when (X, μ) is a standard non-atomic probability space. The paper is organized as follows: First, in Section 2, we will recall various basic notions from the theory of von Neumann algebras and the direct integral theory of unitary representations, and establish a simple lemma that will facilitate hierarchy complexity calculations later.…”
Section: Introductioncontrasting
confidence: 63%
“…This question was answered by Foreman, Rudolph and Weiss in [6], where they gave a negative answer. This answer can be interpreted as saying that determining isomorphism between ergodic transformations is inaccessible to countable methods that use countable amounts of information.…”
Section: Introductionmentioning
confidence: 99%
“…However we were faced at first with the following difficulty. The transformations built in [6] were based on odometers (in the sense that the Kronecker factor was an odometer). It is a well known open problem whether it is possible to have any smooth transformation on a compact manifold that has a non-trivial odometer factor.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, a Bernoulli shift can be effectively recoded into an arbitrary second Bernoulli shift of the same entropy. Ornstein's ideas also played an important role in the construction of counterexamples, such as non-Bernoulli K-automorphisms [Or73] and the recent anti-classification theorems [FW04,FRW11] that study the complexity of the classification problem for measurepreserving transformations up to measure-conjugacy. For example, [FW04] proves it is impossible to classify all measure-preserving transformations up to measureconjugacy by countable structures.…”
Section: Measure Entropymentioning
confidence: 99%